1993
DOI: 10.3758/bf03337371
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward early detection of infection by the AIDS retrovirus among persons at high and low risk

Abstract: Several months prior to the availability of a now-common blood test, homosexual volunteers, in a longitudinal study of their health, and typical college students were questioned about their attitudes toward early detection of acquired immunodeficiency syndrome (AIDS) and toward receiving information about desirable or fear-worthy hypothetical events. Generally, the homosexual volunteers were more interested in receiving information than were the students. Most homosexual volunteers desired human immunodeficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…For example, patients have admitted taking longer to seek help after discovering a symptom if they imagined possible severe consequences of their illness (Safer, Tharps, Jackson, & Leventhal, 1979). However, Fantino, Case, Stolarz-Fantino, Spechko, and McCutchan (1993) found that most of their gay volunteers desired human immunodeficiency virus (HIV) antibody test results and indicated that receiving them would affect their subsequent behavior. Clearly a complex set of contingencies operates in the natural world when decisions must be made involving aversive consequences.…”
Section: Information As Reinforcementmentioning
confidence: 99%
“…For example, patients have admitted taking longer to seek help after discovering a symptom if they imagined possible severe consequences of their illness (Safer, Tharps, Jackson, & Leventhal, 1979). However, Fantino, Case, Stolarz-Fantino, Spechko, and McCutchan (1993) found that most of their gay volunteers desired human immunodeficiency virus (HIV) antibody test results and indicated that receiving them would affect their subsequent behavior. Clearly a complex set of contingencies operates in the natural world when decisions must be made involving aversive consequences.…”
Section: Information As Reinforcementmentioning
confidence: 99%